AGRIBISNIS PADI MERAH CENDANA DALAM MENINGKATKAN KEUNGGULAN KOMPETITIF PETANI - Sukanteri, Ni Putu; Dewi, Luh Gede Panca; Budiasa, I Made; Pratiwi, Luh Putu Kirana (Agriculture Faculty of Flores University, 2025)
Abstract The rice commodity is the main food of the Indonesian people which requires its availability all the time. In line with population growth. Tabanan Regency as a rice producer, especially Jatiluwih Village, Penebel District, is known as an area that produces several types of rice. The rice variety cultivated in the Jatiluwih area is the Jatiluwih Cendana Red Rice variety. The objectives of this research are: To analyze the structure of red rice supply chain activities in Jatiluwih Village. To analyze the competitive advantage of red rice in Jatiluwih Village. The research method used competitive analysis at UD WS Jatiluwih with 13 respondents consisting of farmers, millers and marketers of Cendana red rice. The results of the research show that the supply chain structure for local rice (Cendana red rice) in Jatiluwih Village is: Local rice varieties in Jatiluwih Village are proven to have a relatively high competitive advantage compared to superior rice varieties (Ciherang varieties). Socially, the competitiveness of local varieties of rice is demonstrated by the high position of local varieties among society as consumed by middle and upper class people. Economically, the competitive advantage of local varieties of rice is shown by the relatively high selling price compared to superior varieties.